Telomerase RNA structural heterogeneity in living human cells detected by DMS-MaPseq - Nicholas M. Forino; Jia Zheng Woo; Arthur J. Zaug; Arcelia Gonzalez Jimenez; Eva Edelson; Thomas R. Cech; Silvi Rouskin; Michael D. Stone (Nature Communications)
Abstract Biogenesis of human telomerase requires its RNA subunit (hTR) to fold into a multi-domain architecture that includes the template-pseudoknot (t/PK) and the three-way junction (CR4/5). These hTR domains bind the telomerase reverse transcriptase (hTERT) protein and are essential for telomerase activity. Here, we probe hTR structure in living cells using dimethyl sulfate mutational profiling with sequencing (DMS-MaPseq) and ensemble deconvolution analysis. Approximately 15% of the steady state population of hTR has a CR4/5 conformation lacking features required for hTERT binding. The proportion of hTR CR4/5 folded into the primary functional conformation is independent of hTERT expression levels. Mutations that stabilize the alternative CR4/5 conformation are detrimental to telomerase assembly and activity. Moreover, the alternative CR4/5 conformation is not found in purified telomerase RNP complexes, supporting the hypothesis that only the primary CR4/5 conformer is active. We propose that this misfolded portion of the cellular hTR pool is either slowly refolded or degraded, suggesting that kinetic RNA folding traps studied in vitro may also hinder ribonucleoprotein assembly in vivo.